2007
DOI: 10.1016/j.jneuroim.2007.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chronic nicotine on sciatic nerve injury in the rat

Abstract: Chronic nicotine exposure and the immune response to peripheral nerve injury has not been investigated thoroughly. Rats were exposed to chronic nicotine or saline followed by chronic constriction injury (CCI) of the sciatic nerve. Mechanical sensitivity was measured at various time points and the immune response was investigated at 21 days post-CCI. Chronic nicotine increased mechanical hypersensitivity, microglia activation, and the production of IL-1β, but not the number of immune cells at the site of injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
0
14
1
Order By: Relevance
“…67,75,77,78 Compared with nicotine-naïve rats, nicotine-tolerant rats develop greater mechanical hyperalgesia after spinal nerve ligation or sciatic nerve injury. 79,80 The increased mechanical hyperalgesia was associated with increased spinal dynorphin levels 81 as well as increased production of cytokines centrally and peripherally. 79 Thus, when evaluating the behavioral effects of chronic nicotine exposure a complex interplay among receptor desensitization, overexpression, and neural plasticity in associated nociceptive pathways must be considered.…”
Section: Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…67,75,77,78 Compared with nicotine-naïve rats, nicotine-tolerant rats develop greater mechanical hyperalgesia after spinal nerve ligation or sciatic nerve injury. 79,80 The increased mechanical hyperalgesia was associated with increased spinal dynorphin levels 81 as well as increased production of cytokines centrally and peripherally. 79 Thus, when evaluating the behavioral effects of chronic nicotine exposure a complex interplay among receptor desensitization, overexpression, and neural plasticity in associated nociceptive pathways must be considered.…”
Section: Educationmentioning
confidence: 99%
“…79,80 The increased mechanical hyperalgesia was associated with increased spinal dynorphin levels 81 as well as increased production of cytokines centrally and peripherally. 79 Thus, when evaluating the behavioral effects of chronic nicotine exposure a complex interplay among receptor desensitization, overexpression, and neural plasticity in associated nociceptive pathways must be considered. Furthermore, nicotine withdrawal was associated with hyperalgesia in nicotine-tolerant rodents, 57,82,83 which was reversible by morphine administration.…”
Section: Educationmentioning
confidence: 99%
“…12 One study conducted by Josiah and Vincler 13 suggest that chronic nicotine exposure increases the sensitivity of normal rats to mechanical pressure and compounds nerve injury-induced mechanical hypersensitivity following peripheral nerve injury . Also, in an additional study conducted by Brett et al, 14 it was reconfi rmed that the presence of chronic nicotine further increased nerve injury-induced mechanical hypersensitivity in the periphery. Thus, studies have shown that tobacco possess many negative effects on the healing of many types of tissues and this is of major concern because of the increasing use of tobacco products among the American population.…”
Section: Discussionmentioning
confidence: 86%
“…The reason why cigarette smoking is associated with CubTS is unclear. Numerous studies have suggested that cigarette smoking is associated with peripheral nerve dysfunction . Nicotine has been shown to worsen the effects of ischemia in various tissues through its toxic effects, and it may impair recovery following peripheral nerve injury .…”
Section: Discussionmentioning
confidence: 99%